On the family-group ranks of katydids (Orthoptera, Tettigoniidae) - Braun, Holger (Zootaxa, 2015)
The purpose of this note is to propose minor modifications to recent changes in the classification of katydids, to preserve the stability of the family Tettigoniidae as including all katydids. This concept has been used in the majority of references since it was established long ago (Krauss 1902), with comparatively few exceptions, where all katydid subfamilies were treated as families in superfamily Tettigonioidea.